The Mysterious Benedict Society - 1 - Stewart, Trenton Lee; Ellis, Carson 1975- (New York : Little, Brown, 2007)
After passing a series of mind-bending tests, four children are selected for a secret mission that requires them to go undercover at the Learning Institute for the Very Enlightened, where the only rule is that there are no rules.
Accelerated Reader AR